Evaluación de efectos citotóxicos y genotóxicos con ensayo de micronúcleos en la mucosa bucal de pacientes con aparatología ortodóncica. Revisión de la literatura - Ángeles Estrada, Lucía (2021)
Malocclusions represent an oral health problem, which is resolved by the placement of fixed orthodontic appliances (FOA). This orthodontic appliance causes corrosion and release of metal ions due to the alloys they constitute and due to the prolonged time of treatment. The objective of this work was to analyze the cytotoxic and genotoxic alterations from oral mucosa cells, caused by the use of FOA, reported in the literature and evaluated with micronucleus (MN) test, which is one of the most widely used tests to identify damage to deoxyribonucleic acid (DNA). A review of the literature of the last 10 years was carried out, where nine studies were included, 55% of these studies showed evidence of cytotoxic and genotoxic damage after orthodontic therapy. The increased average in MN due to the use of FOA in these studies, represent values of approximately three-fold more respect to oral cells without treatment, this data is similar to reports of precancerous oral cells that have been reported by other authors. Besides, the articles analyzed reported cell alterations after the first week of the devices placement and indicated a decrease in damage with exposure time. In conclusion, the MN test used in the oral cavity was useful in detecting DNA alterations due to the use of FOA. The data analyzed allow orthodontists to implement improvements in orthodontic therapy.